106 Responding to the First Fall to Prevent the Second: Successful RCT in Reducing Falls using a Person Centred Approach for Older Fallers Presenting to Emergency Departments. (20th December 2019) - Hill, Keith; Barker, Anna; Cameron, Peter; Flicker, Leon; Arendts, Glenn; Brand, Caroline; Morello, Renata; Etherton-Beer, Chris; Forbes, Andrew; Haines, Terence; Hill, Anne-Marie; Hunter, Peter; et al.
Abstract: Background: The majority of older people who fall and present to Emergency Departments (EDs) are reported not to receive guideline level care to reduce future risk of falls. The aim of this randomized controlled trial was to evaluate whether RESPOND, a 6-month telephone-based patient-centred program had an effect on falls and fall injuries in older people presenting to ED after a fall. Methods: 541 older fallers who presented to a WA or Victorian ED were recruited (inclusion criteria: discharged home <72 hours, could walk without hands-on assistance, use a telephone, and no cognitive impairment (MMSE>23). Intervention participants (n=263, mean age=73) received the RESPOND intervention, comprising (1) home-based risk assessment; (2) six months telephone-based education, coaching, goal setting and support for evidence-based risk factor management; and (3) linkages to existing services; while controls (n=260, mean age=73) received usual care. Primary outcomes were falls and fall injuries in the 12-month follow-up. Secondary outcomes included ED presentations, hospital admissions, fractures, death, falls risk, falls efficacy and quality of life. Results: Falls rate was significantly lower in the RESPOND group (incidence rate ratio 0.65 [95%CI 0.43-0.99]; p=0.042). Although there was no significant difference in fall injuries (p=0.374), the rate of fractures was significantly lower in the RESPOND group (p=0.03). There were no significant group differences in other secondary outcomes. Conclusion: The RESPOND falls prevention program reduced falls and fractures, in older people presenting to the ED with a fall. Key learnings for translation include: potential scalability and sustainability of a patient-centred and predominantly telephone-based program.